INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN KESEHATAN DI UPTD PUSKESMAS BETUNG KABUPATEN OKU TIMUR TAHUN 2023 - Vera Sustri Yuliana; Lilis Suryani (LPPM STIKes Mitra Adiguna, 2024)
Permenkes RI No. 30 of 2022, Patient satisfaction is the result of patient assessment of the performance of services provided. UPTD Puskesmas Betung carried out services but found a pile of registration queues, pharmacy waiting rooms, poly waiting rooms, handling complaints of criticism suggestions that have not functioned, surveys or SMIs have not been carried out on health services that have been provided. Thepurpose of this research is to determine the value of SMIs in Puskesmas Betung in 2023.The research method uses a descriptive qualitative approach with the calculation of the Community Satisfaction Index (IKM) in PERMENPAN RB Number 14 of 2017 with a sample of 140 people. Bbased on the calculation of the community satisfaction index of the 9 highest IKM value indicators is the Product Specification Type Service element with an IKM value of 3.32 with an IKM conversion value of 83.00.while the lowest IKM Value is the element of Complaint Handling, Input Suggestions, and Facilities and Infrastructure elements with the same IKM value of 2.97 with an IKM conversion value of 74.25. then the Community Satisfaction Index referring to the Decree of the Minister of State Apparatus Empowerment Number 14 of 2017 obtained an Index number of 79.50 which is in the interval 62.51 – 81.25, so that the quality of health services is at the level of